Informality and migrant entrepreneurs in Cape Town’s inner city - Rogerson, Christian M. (Bulletin of Geography. Socio-economic Series, 2018)
Informality is a defining characteristic of cities in the global South and most especially across the region of sub-Saharan Africa. Policy responses by governments towards the informal economy impact the livelihoods of informal entrepreneurs. In South Africa the informal economy is a critical source of livelihoods in urban areas. Many participants in the informal economy of South Africa’s major urban centres are international migrants, mostly drawn to the country from other parts of sub-Saharan Africa. The objective in this paper is to examine the challenges faced by international migrant entrepreneurs in relation to policy development for the informal economy of the City of Cape Town. The analysis uses qualitative interviews with key stakeholders, documentary sources and secondary surveys. It is revealed that in Cape Town despite a pro-development rhetoric in the inner city there is evidence of a subtle but systematic exclusion of street traders, including of migrant entrepreneurs. Little evidence exists of a coherent analysis by city policy makers to understand and foreground the contributions made by migrant entrepreneurs for the urban economy.